2008
DOI: 10.1111/j.1369-1600.2008.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL STUDY: Lack of effect of chronic dextromethorphan on experimental pain tolerance in methadone‐maintained patients

Abstract: Good evidence exists to suggest that individuals on opioid maintenance for the treatment of addiction (i.e. methadone) are less tolerant of experimental pain than are matched controls or exopioid addicts, a phenomenon theorized to reflect opioid-induced hyperalgesia (OIH). Agonist activity at the excitatory ionotropic N-methyl-D-aspartate (NMDA) receptor on dorsal horn neurons has been implicated in the development of both OIH and its putative expression at the clinical level-opioid tolerance. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Numerous studies have cited dextromethorphan's ability to reduce intra-and post-operative morphine consumption [198][199][200], while others have not replicated these findings [201,202]. Accordingly, Compton et al [203] sought to determine if dextromethorphan would alleviate OIH in methadone maintenance patients. Following a 5-week trial, this group found no effect of dextromethorphan on OIH, as assessed by the cold pressor test and electrical stimulation pain measures [203] (Table 3).…”
Section: Dextromethorphanmentioning
confidence: 94%
See 1 more Smart Citation
“…Numerous studies have cited dextromethorphan's ability to reduce intra-and post-operative morphine consumption [198][199][200], while others have not replicated these findings [201,202]. Accordingly, Compton et al [203] sought to determine if dextromethorphan would alleviate OIH in methadone maintenance patients. Following a 5-week trial, this group found no effect of dextromethorphan on OIH, as assessed by the cold pressor test and electrical stimulation pain measures [203] (Table 3).…”
Section: Dextromethorphanmentioning
confidence: 94%
“…Accordingly, Compton et al [203] sought to determine if dextromethorphan would alleviate OIH in methadone maintenance patients. Following a 5-week trial, this group found no effect of dextromethorphan on OIH, as assessed by the cold pressor test and electrical stimulation pain measures [203] (Table 3). To date, no other clinical trials have investigated dextromethorphan in the context of OIH during concurrent opioid use.…”
Section: Dextromethorphanmentioning
confidence: 99%
“…24 in clinical settings, nmDa receptor antagonists such as dextromephorthan have been proposed to reduce tolerance, but results overall have been mixed. 25,26 opioid-induced hyperalgesia studies in animal models have indicated that opioid exposure can induce a paradoxical increase in pain sensiti vity and potentially exacerbate pre-existing pain. 22,23 the phenomenon of opioid-induced hyperalgesia is thought to be predominantly the result of central sensitiza tion of pronociceptive pathways and is associated with reduced nociceptive threshold.…”
Section: Conditioned Opioid Responsesmentioning
confidence: 99%
“…Using healthy volunteers (instead of persons physically dependent on opioids) for laboratory examinations of opioid analgesia reduces confounds and allows investigators to make inferences more clearly about analgesic effects and pain mechanisms. The few studies reporting pain-related outcomes in persons dependent on opioids (typically methadone or buprenorphine-treated individuals) are important because they have demonstrated significant differences in pain and opioid analgesia between these persons and healthy controls 6, 8, 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The PPT has been used to assess analgesic efficacy of drugs such as ibuprofen, ketamine, tramadol, and codeine 29 . The CPT has been used frequently for hyperalgesic testing in populations dependent on opioids 8, 7 , and it is sensitive to opioid analgesia with morphine 28 , oxycodone 16 , fentanyl 21 , and tramadol 12, 26 .…”
Section: Introductionmentioning
confidence: 99%